Test-retest reliability and validity of three different agility tests for various team sports in young male athletes - Kutlu, M.; Dogan, Ö. (Central European Journal of Sport Sciences and Medicine, 2018)
The purpose of this study is to examine the reproducibility of three different agility tests in basketball, soccer and water polo team sports. To determine the reliability 44 young male athletes (Basketball age 16.5 ±0.6, height 177.9 ±7.7 weight 70.0 ±7.1; Soccer age 16.3 ±0.5, height 169.2 ±5.0, weight 71.2 ±7.9; Water Polo age 17.1 ±0.7, height 181.3 ±6.7, weight 76.7 ±7.2) performed 3 different agility tests (Zig-Zag, Illinois and AS) on two occasions 1 wk. apart for test-retest. Sprint time scores were analyzed for each test. To determine the reliability Paired Sample T-test and Pearson Correlation Statistics were computed. Scores of teams were compared with ANOVA statistics to determine the difference. Test results showed that there was no significant difference between the two occasions for all agility test on subjects and teams (p > 0.01). There was higher correlation between test-retest values of subjects (r = 0.90-0.97). Three different agility tests were found valid in determining agility with significant moderate level correlation. (r = 0.36-0.44; p < 0.01). Differences among sport branches were found significant for agility scores (p < 0.05). All three agility tests are reliable and valid for team sport athletes. Soccer players had better scores than other branches in soccer specific test (AS). This study showed that sport specific agility tests are more useful than general agility tests.